Grid-Forming Current-Source Converter for a Full-Scale Wind Energy Conversion System - Amr Ahmed A. Radwan; Mahmoud Awad Elshenawy; Yasser Abdel-Rady I. Mohamed; Ehab F. El-Saadany (IEEE Open Journal of Power Electronics)
This paper presents a grid-forming (GFM) current-source (CSC)-based full-scale wind energy conversion system with detailed small-signal modeling, dynamic analysis, and systematic control design approach. The system comprises 1) a machine-side vector-controlled CSC to regulate the power extracted from the permanent-magnet synchronous generator-based wind turbine, where a practical two-mass drivetrain model is adopted, and 2) a grid-side CSC controlled by a GFM scheme to support the grid and regulate the dc-link current to maintain a stable delivery of the extracted wind power. A detailed small-signal state-space model of the overall CSC-based system is developed to investigate the system's stability under different practical parameters, such as wind power reserve, control parameter, and short-circuit ratio variation. The equivalent dc-side impedances of the grid and machine-side CSCs are also developed and used to characterize the dc-link stability using the Nyquist stability criterion. A systematic design approach for the control parameters is presented. Nonlinear-model time-domain simulations are presented to verify the analytical results and assess the performance under various operating conditions, such as grid disturbances, faults, and parameter uncertainty. This study shows that the GFM CSC system provides stable operation under weak and very weak grid conditions and robust performance under fault conditions compared to a similar GFM voltage-source converter system.